The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1099/mic.0.000216
|View full text |Cite
|
Sign up to set email alerts
|

A pressure gradient facilitates mass flow in the oomycete Achlya bisexualis

Abstract: We have used a single cell pressure probe and observed movement of microinjected oil droplets to investigate mass flow in the oomycete Achlya bisexualis. To facilitate these experiments, split Petri dishes that had media containing different sorbitol concentrations (and hence a different osmotic potential) on each side of the dish were inoculated with a single zoospore. An initial germ tube grew out from this and formed a mycelium that extended over both sides of the Petri dish. Hyphae growing on the 0 M sorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Growth rates of oomycetes and fungi can be variable, typically ranging from 1 -10 µm/min 40 ). For the isolate of A. bisexualis used in the current study, rates around 6-8 µm/min have been previously reported 41 , which is consistent with those observed on our platform.…”
Section: Hyphal Growth and Morphologysupporting
confidence: 91%
“…Growth rates of oomycetes and fungi can be variable, typically ranging from 1 -10 µm/min 40 ). For the isolate of A. bisexualis used in the current study, rates around 6-8 µm/min have been previously reported 41 , which is consistent with those observed on our platform.…”
Section: Hyphal Growth and Morphologysupporting
confidence: 91%
“…A. bisexualis zoospores were produced through a starvation cycle of A. bisexualis [16]. In brief, six inoculum plugs from a fresh culture growing edge of A. bisexualis were evenly spread around on a nappy liner, which was placed on peptoneyeastglucose (PYG) agar Petrie dish.…”
Section: Methodsmentioning
confidence: 99%
“…Then it was swirled on an orbital shaker at 150 rpm for 24 hours at 26 °C. The PYG broth in the flask was exchanged with a mineral salt solution [16] six times and swirled again at 150 rpm at 26 °C overnight. The content of the flask was filtered by sterile Kimwipes and vortexed for 10 s to collect fully developed zoosporangia and released zoospores in solution.…”
Section: Methodsmentioning
confidence: 99%
“…Unless Pfeffer's mechanism is a fallacy we all fell victim to, hyphae of fungi with perforated septa are free‐living sieve tubes, biophysically speaking. Osmotically induced mass flow in such hyphae is an established fact (Ternetz ; Jennings ; Abadeh and Lew ; Muralidhar et al ), but phloem and fungal physiologists seem to enjoy limited scientific interaction, to judge from the reference lists in their papers. We feel that the potential conceptual and methodological benefits that can result from occasional shifts of our focus from the phloem of higher plants to other systems showing translocation by Pfeffer's mechanism might be underestimated.…”
Section: Plausible But Not Provenmentioning
confidence: 99%